PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) DI SEKOLAH DASAR - Defita Berliani Putri; Nela Rofisian; Fauziyyah Muna Karomah (Global Education Trends, 2023)
This research aims to find out how to apply the Realistic Mathematics Learning (RME) approach so that it can improve student learning outcomes in learning large whole number mathematics. This type of research uses Classroom Action Research (PTK). The subjects of this research were 19 class IV students at SD Negeri 1 Gumul in the odd semester of the 2023/2024 academic year. The instruments used are observation sheets, documentation, and student learning outcomes tests. The results of this research show that there is an increase in student learning outcomes by using teaching aids to explain mathematics learning about large whole numbers. Student learning outcomes can also be improved by reminding them of the material from previous meetings and linking learning to everyday (real) life. Keywords: Learning outcomes; RME.